2019
DOI: 10.14371/qih.2019.25.2.16
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Care Performance of Three Types of Medical Institutions: A Public Survey using the Korean Primary Care Assessment Tool

Abstract: These authors contributed equally this work. *These authors also contributed equally to this work.Purpose: The healthcare system of South Korea is at the extreme of the dispersed system. Few regulations limit patients from directly visiting higher-level medical institutions for primary care sensitive conditions. As a result, similar to local clinics, general and tertiary teaching hospitals also provide diverse primary care services. Our study aimed to examine the general public's perceptions of their primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Concentration of patients in tertiary hospitals causes not only the economic problem in terms of waste of health care resource and the loss of opportunity cost for other hospitals but also the delay of timely treatment. Previous studies showed that patients tend to make choices based on hospital size, facility, modernity, and professional credibility 7 , 8 . The phenomenon of the concentration in tertiary hospitals might derive due to the lack of information (such as clinical outcomes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration of patients in tertiary hospitals causes not only the economic problem in terms of waste of health care resource and the loss of opportunity cost for other hospitals but also the delay of timely treatment. Previous studies showed that patients tend to make choices based on hospital size, facility, modernity, and professional credibility 7 , 8 . The phenomenon of the concentration in tertiary hospitals might derive due to the lack of information (such as clinical outcomes).…”
Section: Discussionmentioning
confidence: 99%
“…With no strict gatekeeping system, it is relatively easy for patients to access secondary care in tertiary hospitals. In addition, patients generally prefer tertiary hospitals to non-tertiary hospitals because they believe that the quality of care that is provided by tertiary hospitals is better than that of non-tertiary hospitals 7 . These engender the concentration of patients in tertiary hospitals and results in the waste of health care resource and delay of timely treatment 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Such high utilisation might be due to the physical proximity of the clinics and satisfaction with the services offered, although such services were limited in scope (39). (50)(53)…”
mentioning
confidence: 99%